Participatory climate information services benefitting over 105,000 farmers in Rwanda - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Through a CCAFS-led effort to scale up participatory training on climate services in Rwanda, around 105,000 Rwandan farmers were trained on accessing, understanding and using climate services. The approach involved training trainers, filling gaps in climate service records and developing online map tools.